Extracorporeal Membrane Oxygenation May Improve Outcomes After Resuscitative Thoracotomy: A National Trauma Data Bank Analysis. Issue 10 (October 2021) - Owattanapanich, Natthida; Inaba, Kenji; Allen, Brad; Lewis, Meghan; Henry, Reynold; Clark, Damon; Matsushima, Kazuhide; Strumwasser, Aaron
Background: Albeit low survival rates, resuscitative thoracotomy (RT) is considered standard for selected trauma patients. Because it has potential for rapid cardiopulmonary rescue, extracorporeal membrane oxygenation (ECMO) may augment RT. The aim of this study was to identify the impact of ECMO on trauma patients that recently underwent RT after injury. Study Design: All patients who underwent RT were identified from the National Trauma Data Bank (2007-2017). Patients were excluded if they died within 60 minutes, underwent delayed ECMO, and/or had missing data. Delayed ECMO group was defined as those patients undergoing ECMO after 1 hour following RT. Results: Out of 8 694 272 injured patients, 10 106 (.1%) underwent RT. Median age was 31 years [23-45], 86% male. Penetrating injury was the dominant mechanism (62%). Of these, .6% (23) underwent immediate ECMO. Extracorporeal membrane oxygenation patients were significantly younger (23[17-33] vs. 31[23-46], p .003) and had significantly higher chest abbreviated injury scale scores (5[4-5] vs. 3[3-4], P < .001). Extracorporeal membrane oxygenation patients achieved significantly higher rate of return of spontaneous circulation (96% vs. 70%, p .007) and had nonsignificant trend of improved mortality (52% vs. 63%, p .260). Conclusion: Immediate ECMO may be a useful therapeutic modality after RT. It achieves higher ROSC rates with opportunity for improved survival. Future prospective study is warranted.